Globalizing domain-specific languages : International Dagstuhl Seminar, Dagstuhl Castle, Germany, October 5-10, 2014 : revised papers /: International Dagstuhl Seminar, Dagstuhl Castle, Germany, October 5-10, 2014 : revised papers. (2015) - Unknown
No abstract available